O eu objeto: um estudo metapsicológico do narcisismo em Freud - Zuin, Leonardo Sene (Universidade Federal de São Carlos, 2022)
This work comprises a qualitative research on narcissism in Freud's work. Treating since its origin, in Freudian studies of the support relationships of sexual instincts on the instincts of self-preservation and autoeroticism, so that narcissism leads to the end of the first instinctual theory, the impacts of narcissism in Freud's theory, the melancholy as disease of narcissistic basis, until the adoption of the second instinctual theory. Among the conclusions of this work, there is the idea that, even after decreasing in terms of importance, narcissism remains a vital axis for the understanding of psychosexual development in Freud, and of his theory as a whole.
The object-ego: a metapsychological study of narcissism in Freud
Keywords: Narcisismo; Libido; Psicanálise; Freud; Narcissism; Psychoanalysis; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO